Schools as Community Hubs 2023
DOI: 10.1007/978-981-19-9972-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Urban Schools as Social Infrastructure

Abstract: Re-thinking urban schools as part of an integral network of social infrastructure in cities presents new opportunities for mixed-use educational spaces at the heart of urban development. Yet these opportunities to leverage school assets to better integrate with, and enhance, their localities are often being missed. This chapter explores the value that schools can offer, not just for children, but for wider neighbourhood residents. While understanding that there is no one-size-fits-all approach, we report on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Increased educational opportunities are linked to well-developed urban infrastructure, whereas poor infrastructure restricts access to high-quality education and exacerbates inequality (de Freitas Marangão et al, 2022). Studies have indicated that state-of-the-art physical amenities in schools foster a learning environment and improve students' academic performance (Boys & Jeffery, 2023;Posțan, 2022;Sebu, 2023;Yangambi, 2023). The accessibility and availability of educational resources and infrastructure close to a person's home are crucial for lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…Increased educational opportunities are linked to well-developed urban infrastructure, whereas poor infrastructure restricts access to high-quality education and exacerbates inequality (de Freitas Marangão et al, 2022). Studies have indicated that state-of-the-art physical amenities in schools foster a learning environment and improve students' academic performance (Boys & Jeffery, 2023;Posțan, 2022;Sebu, 2023;Yangambi, 2023). The accessibility and availability of educational resources and infrastructure close to a person's home are crucial for lifelong learning.…”
Section: Introductionmentioning
confidence: 99%